EFEKTIFITAS STRATEGI PEMBELAJARAN SISWA AKTIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Nofiansyah, Wahyu (JURNAL E-DUMATH, 2016)
The purpose of this study is to determine the effectiveness of activestudent learning strategies to the students learning achievements on thelines and angles material. The population this study is all of the seventhgrade students of SMP IT Al-Munir Sukoharjo Pringsewu in theacademic year 2014-2015 that consist of 24 students. This study 5students as a respondents and 19 students as a sample. The datacollecting technique used was test and test description consists of 3items. Furthermore, the data has been analyzed using descriptive t test.The results of analysis data, that there are differences between theresults of students mathematics learning after a given learning by usinglearning strategies students active with the chief engineer, and theaverage results of students mathematics learning after being given anactive student learning strategies more than Minimum CompletenessCriteria at 65 so it can be concluded that active student learningstrategies is an effective learning of the results of students mathematicslearning.Keywords: effectiveness of active student learning strategies,students learning achievements